A Method for Parasagittal Sectioning for Neuroanatomical Quantification of Brain Structures in the Adult Mouse. Issue 3 (26th June 2018) - Collins, Stephan C.; Wagner, Christel; Gagliardi, Léo; Kretz, Perrine F.; Fischer, Marie‐Christine; Kessler, Pascal; Kannan, Meghna; Yalcin, Binnaz
Abstract: In this article, we present a standardized protocol for fast and robust neuroanatomical phenotyping of the adult mouse brain, which complements a previously published article (doi: 10.1002/cpmo.12 ) in Current Protocols in Mouse Biology . It is aimed at providing an experimental pipeline within an academic research setting from experimental work to data analysis. Our analysis focuses on one single parasagittal plane, covering the majority of brain regions involved in higher order cognitions such as the cortex, hippocampus, and cerebellum, for a total of 166 parameters of area, length, and cell‐level measurements in contrast to 78 parameters in our previously published coronal screen. Benefits of using parasagittal analysis for large‐scale neuroanatomic screens are discussed. © 2018 by John Wiley & Sons, Inc.